Scientific Publication as a Sustainable Professional Development Effort from the Perspective of ES Teachers - Mardiyah, Ainul; Rahmi, Tysa Sufia; Yusra, Alfajri; Rusdinal, Rusdinal; Gistituati, Nurhizrah (Postgraduate School, Universitas Negeri Padang, 2023)
Scientific publication is one of the activities in primary school teachers' sustainable professional development efforts. In addition, this scientific publication activity is also useful as material for teacher promotion professional improvement, and teacher performance. This study aims to collect information, describe, and analyze scientific publication activities to develop sustainable professionalism as well as inhibiting factors and solutions that can be provided in overcoming the problems of teachers' scientific publication skills. The research data collection used Google Forms distributed to several teachers who are civil servants about writing scientific papers for teacher promotion and was also supported by direct interviews with several teachers. The research data were analyzed descriptively in the form of activities to analyze, describe, and summarize the phenomena discussed. Some of the problems found in the scientific publication of teachers are limited time due to too many activities, lack of ideas and motivation to write, lack of understanding of teachers in writing and publishing scientific papers, and lack of references or related reading materials.